Characterization of undifferentiated spermatogonia and the spermatogonial niche in the lambari fish Astyanax altiparanae - de Paiva Camargo, Marília; Cassel, Mônica; Oliveira de Jesus, Lázaro Wender; Nóbrega, Rafael Henrique [UNESP]; Borella, Maria Inês (Elsevier, 2017)
Undifferentiated type A spermatogonia are the foundation of fish spermatogenesis. This cell population includes the spermatogonial stem cell population, which is able to either self-renew or differentiate into cells that will generate the male gamete — the spermatozoa. Spermatogonia stem cells are located in a specific region of the testes known as the spermatogonial niche, which regulates spermatogonial stem cell function. This study characterizes undifferentiated type A spermatogonia and their S-phase label-retaining cell properties in Astyanax altiparanae testes. This is a fish species of substantial commercial, environmental, and academic importance. Two types of undifferentiated spermatogonia have been described in A. altiparanae testis: Aund* and Aund. Among the main differences observed, Aund* spermatogonia have an irregular nuclear envelope, decondensed chromatin, one or two nucleoli, and nuages in the cytoplasm; meanwhile, type Aund have a round nucleus. Aund* is preferentially distributed in areas neighboring the interstitial compartment, whereas Aund is located in the intertubular area. Finally, this study found that undifferentiated type A spermatogonia were able to retain BrdU over a long chase period, suggesting that these cells have a long cell cycle and potential stem cell candidates among them. Based on these findings, undifferentiated type A spermatogonia may be characterized as putative stem cells in A. altiparanae testis. This work will contribute to further studies on the stem cell biology of this promising Neotropical experimental model.
Keywords: Label-retaining cells; Morphology; Morphometry; Spermatogonial niche; Stem cell